COMPARISON OF CONTINUOUS AMBULATORY PERITONEAL DIALYSIS TENCKHOFF CATHETER INSERTION (OPEN SURGERY VS LAPAROSCOPIC) – A CASE CONTROL STUDY - Kusumajaya, Christopher; Tjahjodjati (Indonesian Journal of Urology, 2025)
Objective: This study aims to investigate post-operative complication rate of Tenckhoff catheter placement methods between open surgery and laparoscopic. Material & Methods: This is a case control comparative study reviewed from the medical records of patients who required insertion, removal, or repairment of Tenckhoff catheter for the provision of CAPD at Hasan Sadikin Bandung general hospital between January 2015 to December 2020. Clinical outcome and complication were compared between the open surgery and laparoscopic group. Results: We obtained 30 patients who required insertion of a Tenckhoff catheter for the provision of CAPD, 15 patients by open surgery and 15 patients by laparoscopic technique. Insertion of Tenckhoff catheter using open surgery have a higher risk of catheter migration (p=0.049; O R=3.25) and infection (p=0.014; OR=12.25) compared to laparoscopic. Discussion: Laparoscopic technique facilitates omentectomy, allows better fixation under direct visualisation, and for lysis of adhesions to increase peritoneal surface. Conclusion: Tenckhoff catheter insertion by using laparoscopic surgery tend to have better outcome compared to open surgery, with lower risk of catheter migration and infection. Keywords: Tenckhoff catheter, laparoscopic, CAPD.